Pickled histories, bottled stories: Recuperative narratives in the God of Small Things - Sheena Patchay (Journal of Literary Studies, 2001)
This article explores the various ways in which The God of Small Things (Arundhati Roy 1997) interrogates and rewrites versions of histories. By blurring the boundaries between the personal and the political, the novel exposes official, documented History and suggests that such History rests on and empowers itself at the expense of subaltern discourses that have been (deliberately) marginalised. This article discusses the various ways in which history, memory and silences resurface in a range of narrative situations in the novel so that they may be remembered and rewritten.